Marketing Strategies for Sustainable Development in Developing Countries - Samuel Niyi and Ogunode Philips Olatunde, Abereola (British Journal of Marketing Studies, 2018)
As the traditional role of corporate entities have been challenged by an increased number of demands from society, organizations roles are no longer limited to generate profits by supplying products or services. Instead, they are expected to play the role of responsible co-citizens of the community, taking social and environmental responsibility for the consequences of their actions. Implementing sustainable practices into business strategies is considered beneficial for both organizations and society, as it brings organizations opportunities for growth and development, as well as a more sustainable future for society. More so, the success or failure of any business is said to rests in part on the nature and types of marketing strategy they employ.A cross-sectional survey design was put in place for the study. The unit of analysis was organizations while the owner/managers of SMEs were the respondents. Systematic, simple random and snowbell sampling techniques were employed to collect the needed data for the study. A sample size of 200 SMEs covering all sectors that exist in the study area was drawn from a population of 522 SMEs. Inferential statistics was used to empirically and statistically analyze the data collected for the study with the aid of Statistical Package for Social Science (SPSS) version 20. Regression analysis was used to test the hypotheses. The study revealed that a positive relationship exist between Customer Relationship Management (CRM) and Sustainability Marketing (SM) and the relationship is statistically significant (p<0.05).Also, it shows that a positive relationship exist between Sustainability Marketing (SM) and Competitive Advantage and the relationship is statistically significant (p<0.05.It was recommended that SMEs operating in the Nigerian market should endeavour to communicate sustainable practices strategies internally in order to form effective sustainability strategies in all business decisions.